KEPEMIMPINAN KEPALA DESA DALAM PEMBERDAYAAN MASYARAKAT (STUDI DI DESA PARIT KEBUMEN DAN DESA TELUK LECAH KECAMATAN RUPAT KABUPATEN BENGKALIS TAHUN 2017) - Abdul Rahim; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The leadership of the Head Village in empowering village communities is needed in helping the community to be more independent and empowered. Kebumen Parit Village is a division of Teluk Lecah Village, but the Parit Kebumen Village is faster to succeed and is the best village in Bengkalis Regency year 2016 and 2017. The research aims to describe the leadership of the Head Village in empowering the community of Parit Kebumen Village and Teluk Lecah Village in 2017. This study uses leadership theory in accordance with the Head Village leadership type and situational leadership theory to help answer the objectives.This study uses a qualitative approach. Data was collected using field studies. Data collected through informants purposively. Data collection techniques use field research, interviews, and documentation studies. While the data analysis uses descriptive data analysis techniques.This study uses a qualitative approach. Data is collected using field research. Data is collected through informants purposively. The technique of collecting data uses field research, interviews, and documentation studies. While data analysis uses descriptive data analysis techniques.The results of the study show that the leadership of the Head of the Village of Parit Kebumen manages power for the benefit of many people, all forms of empowerment programs ranging from government and development are carried out to empower rural communities. While the leadership of the Teluk Lecah Village Chief was run normatively according to the main tasks and functions of the Head Village so that the empowerment program in the field of government and development followed the existing rules. The effort of the Parit Kebumen Head Village to embrace all parties, village officials and the community so that they succeeded in becoming the best village.Keywords: Leadership Head Village, Community Empowerment.